2016
DOI: 10.1364/optica.3.000803
|View full text |Cite
|
Sign up to set email alerts
|

Interscale mixing microscopy: far-field imaging beyond the diffraction limit

Abstract: We present an analytical description and an experimental realization of interscale mixing microscopy, a diffractionbased imaging technique that is capable of detecting wavelength/10 objects in far-field measurements with both coherent and incoherent broadband light. This method aims at recovering the spatial spectrum of light diffracted by a subwavelength object based on far-field measurements of the interference created by the object and a finite diffraction grating. A single measurement, analyzing the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…5, illustrating the robustness of the developed classifier that has been trained exclusively on theory-generated data that is capable of detecting each object (with smallest available to us dimension of 185 nm) with 532nm laser light. Note that while coherent laser light has been used in this work, our previous analysis [26] has indicated that gratings-assisted imaging works with incandescent white-light illumination. Similar to the theoretical studies reported above, not all the objects are classified with the same accuracy.…”
Section: Fig 4 Convergence Of the Classifiers Classification Accuracy...mentioning
confidence: 99%
“…5, illustrating the robustness of the developed classifier that has been trained exclusively on theory-generated data that is capable of detecting each object (with smallest available to us dimension of 185 nm) with 532nm laser light. Note that while coherent laser light has been used in this work, our previous analysis [26] has indicated that gratings-assisted imaging works with incandescent white-light illumination. Similar to the theoretical studies reported above, not all the objects are classified with the same accuracy.…”
Section: Fig 4 Convergence Of the Classifiers Classification Accuracy...mentioning
confidence: 99%
“…The remaining integral in expression (13) over the radial distance variable, u, over the range (0, 1) can now be carried out by substituting (14) into that expression, with the result…”
Section: Integral Equation For the Coefficient Function In The Fourie...mentioning
confidence: 99%
“…More recently, the use of coherent detection techniques [14,15] have promised to enable true super-resolution of closely spaced point sources via quantum-correlated, optical centroid measuring states [16][17][18] and wavefront projections [19][20][21][22][23][24][25][26][27]. These latter papers, led principally by the work of Tsang and collaborators [19], have provided the most fundamental, quantum mechanical estimation-theoretic limits of superresolution possible by any method and their realization in the context of pointsource imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This approach resembles object recovery in deconvolution microscopy [19]. It is also similar to the interscale mixing microscopy (IMM) [39,8], although we do not share the opinion [8] that a binary grating nonoverlapping with the object could introduce mixing of the evanescent spectrum of the object into the far-field pattern. In fact this concept is not upheld in [7].…”
Section: Introductionmentioning
confidence: 96%
“…Superresolving optical microscopy becomes increasingly important in medical and biological applications, in nanotechnology, material science etc. Recent advances in computational imaging [1,2] and deep learning [3] reopen the question of how much resolution can be enhanced by data completition methods [4,5,6,7,8]. While scanning near-field optical * rafalk@fuw.edu.pl microscopy [9] as well as techniques based on fluorescence microscopy [10] allow to reach a deeply sub-wavelength resolution down to the order of several nanometers, the resolution of classical optical imaging is restricted by the Abbe diffraction limit.…”
Section: Introductionmentioning
confidence: 99%